Morphological features of the wall of the fallopian tubes newborns - Slavcheva, O. S. (Запорізький державний медичний університет, 2019)
The formation of organs of the reproductive system is an urgent problem of embryology, histology and gynecology. Of particular interest are the data on histotological and topographical features of the fallopian tubes in ontogenesis. According to the literature, the wall thickness of the fallopian tube in the dynamics of the fetal period increases towards from the funnel to the uterine part. In women of reproductive age thickness of the muscular shell of the fallopian tubes is the most pronounced in the isthmic part, as compared to other departments and forms a circular muscle, which acts as a sphincter. In the scientific literature there are no data on the morphometric parameters of the human fallopian tube wall in an early postnatal ontogenesis. Objective. A study of the morphological features of the wall of the fallopian tubes of full-term newborns.
Keywords: тези доповідей